Advances in Engineering Research and Innovations - Mohd Faizul Bin Mohd Sabri; Noorhayati Idros; Hanie Nadia Shasmin (Advances in Engineering Research and Innovations, 2025)
This book synthesizes a broad array of cutting-edge research across diverse fields of engineering and technology, each chapter reflecting innovative strides toward addressing global challenges. From sustainable materials to automation, energy efficiency, and advanced manufacturing techniques, the studies delve into the transformative potential of science and engineering. The compilation begins with advancements in materials science, exploring novel approaches to sustainable energy, carbon capture, and industrial process optimization. This foundation is enriched by investigations into composite materials, thermal systems, and renewable resources, showcasing interdisciplinary solutions for ecological and industrial demands. Further chapters examine material testing, characterization, and corrosion engineering, presenting breakthroughs in enhancing durability, efficiency, and environmental safety. Progress in robotics and AI-driven automation underscores the increasing integration of intelligent systems in enhancing productivity and safety across sectors. Special attention is given to sustainable energy systems, fluid dynamics, and advanced manufacturing, reflecting global imperatives for innovation in renewable energy, efficient processes, and resilient materials. Contributions in biomechanics, biomedical engineering, and environmental sustainability demonstrate the profound impact of technology on human health, safety, and ecological balance. In unison, these chapters illustrate the role of engineering and science in addressing the pressing demands of a rapidly evolving world, paving the way for a sustainable and technologically advanced future. Each study stands as a testament to the ingenuity and determination of researchers committed to improving the quality of life and fostering global progress.